LncRNA-Encoded Peptide: Functions and Predicting Methods - Xing, Jiani; Liu, Haizhou; Jiang, Wei; Wang, Lihong (Frontiers in Oncology, 2021)
Long noncoding RNA (lncRNA) was originally defined as the representative of the noncoding RNAs and unable to encode. However, recent reports suggest that some lncRNAs actually contain open reading frames that encode peptides. These coding products play important roles in the pathogenesis of many diseases. Here, we summarize the regulatory pathways of mammalian lncRNA-encoded peptides in influencing muscle function, mRNA stability, gene expression and so on. We also address the promoting and inhibiting functions of the peptides in different cancers and other diseases. Then we introduce the computational predicting methods and data resources to predict the coding ability of lncRNA. The intention of this review is to provide references for further coding research and contribute to reveal the potential prospects for targeted tumor therapy.